Into the Deep End: From Madness-as-Strategy to Madness-as-Right - Miguel Núñez de Prado-Gordillo (European Journal of Analytic Philosophy)
A central notion in Mad Pride activism is that “madness is a natural reaction” (Curtis et al. 2000, 22). In Madness: A Philosophical Exploration (2022), Justin Garson provides a compelling exploration and defence of this idea through the book’s central concept: madness-as-strategy, i.e., the view of madness as “a well- oiled machine, one in which all of the components work exactly as they ought” (1). This contrasts with the dominant view in 20th- and 21st-century psychiatry, madness-as-dysfunction, which understands madness as a failure of function. The paper provides a critical analysis of the notion of madness-as-strategy as a political tool, pointing out its main virtues and limitations in terms of Garson’s overarching political project: to carve out the conceptual landscape of madness in ways that pay tribute to mad people’s own perspectives. The analysis draws on two central commitments of contemporary neurodiversity theory: a) its relational-ecological model of cognitive (dis)ability; and b) its non-essentialist, sociopolitical critique of the “normalcy paradigm”. I argue that these two insights contribute to both expand the applicability of madness- as-strategy and highlight its limitations as a tool for the political struggles of mad, cognitively divergent, and mentally ill or disabled people. The paper concludes by outlining a way to move beyond both madness-as-dysfunction and madness-as-strategy, toward what I call madness-as-right.